MORPHOLOGICAL AND MORPHOMETRIC CHARACTERISTICS OF THE THYMUS AND BONE MARROW OF OUTBRED RATS DURING POSTNATAL ONTOGENESIS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This study investigated the morphological and morphometric characteristics of the thymus and bone marrow in outbred rats during postnatal ontogenesis. Histological and morphometric analyses were performed on tissues obtained from newborn, 2-month-old, and 4-month-old rats of the control group. The results revealed age-dependent structural changes characterized by gradual thickening of the thymic capsule and trabeculae, development of vascular components, redistribution of thymocytes between cortical and medullary zones, and signs of early involution processes. Morphometric indicators confirmed progressive structural maturation and functional reorganization of central immune organs during postnatal development. The obtained data may serve as baseline reference values for further experimental and immunomorphological studies.